Fintech for Inclusion or Exclusion? The Impact of Digital Credit Scoring Algorithms on Access to Finance for the Urban Poor - Samantha Gonzales; Luis Santos; Andres Villanueva (Yayasan Adra Karima Hubbi, 2025)
Background. The rise of fintech and digital financial services has transformed access to finance, particularly for underserved populations. However, concerns have emerged regarding the potential for digital credit scoring algorithms to either facilitate inclusion or perpetuate exclusion, especially for the urban poor. In many developing countries, these algorithms are being used to assess creditworthiness, but their reliance on big data, social media activity, and other non-traditional factors raises questions about fairness and transparency. Purpose. This study aims to evaluate the impact of digital credit scoring algorithms on access to finance for the urban poor, focusing on whether these algorithms contribute to financial inclusion or exclusion. Method. The research adopts a mixed-methods approach, combining quantitative data analysis from fintech platforms with qualitative interviews from urban poor individuals in Indonesia. Results. The findings reveal that while digital credit scoring has improved access to financial products for some, it has also disproportionately excluded individuals with limited digital footprints or those lacking access to traditional banking systems. Conclusion. The study concludes that digital credit scoring, if not carefully regulated, risks exacerbating financial inequality. Policy recommendations include enhancing transparency, addressing biases in algorithmic decision-making, and ensuring greater financial literacy to bridge the digital divide.